Journalism and justice in the Oklahoma City bombing trials - Nye, Chad F., 1970- (Law and society (New York, N.Y.), 2014)
Nye examines the fair trial/free press issues in one of America's most infamous criminal cases - the Oklahoma City bombing. The trials of Timothy McVeigh and Terry Nichols were the first, and to date only, federal criminal trials conducted with live, closed-circuit cameras in the courtroom. More than 2,000 national and international journalists covered the trials through a media consortium. Through interviews with the lead attorneys for both McVeigh and Nichols, Nye exposes the difficulties defense attorneys faced defending their clients in the courtroom and also in the court of public opinion.